Elaboração, aplicação e análise de aulas em perspectiva dialógica de ensino-aprendizagem sobre Sistemática Vegetal para o ensino fundamental I - Oliveira, Matheus Fernando Custódio de (Universidade Federal de São Carlos, 2025)
Botany is a science that encompasses all aspects related to plants, and is important and forms part of the major area of Biology. Plant Systematics is the main constituent axis of Evolutionary Biology. However, regarding the teaching and learning aspects of this axis in Basic Education schools, several authors have raised questions and problems, identifying it as ineffective, repetitive and memorizing. Despite this, there are few studies that contribute to overcoming the barriers already known. Thus, this research presents the development, application and analysis of classes in a dialogical perspective of teaching and learning about Plant Systematics for Elementary Education. For this, the classes were based on Freire's Thematic Approach, being divided into three Pedagogical Moments: problematization, organization of knowledge and application of knowledge. Successful Educational Actions were incorporated to compose the stages. The research was conducted in a municipal school in the city of Limeira/SP, in a 5th grade Science class. Based on the Communicative Methodology, the data were collected, analyzed and agreed upon through the Communicative Observation Diary and the Communicative Focus Group. Furthermore, the knowledge present in the students' records during the activities was quantified based on the presence of key words in the answers, accounted for by the correction/verification of learning impressions and analyzed according to the typology of knowledge proposed by Eric Gutstein, evidencing an approval rate of 72.7%, that is, above the institutional school average (5). As a result of this analytical process, the results of learning impressions were compared with the exclusionary and transformative elements identified in the diary and in the focus group, verifying the contributions in relation to Dialogical Learning, as a theoretical methodological framework, and in relation to the presence of Classical, Community and Critical knowledge on Plant Systematics, as well as that brought by the students from reading the world. Furthermore, the interference of variables was considered, such as teaching experience and experience with Successful Educational Actions, as an analytical process of the practice of the ambiguous role of teacher and researcher.
Preparation, application and analysis of classes in a dialogical perspective of teaching-learning on Plant Systematics for elementary school
Keywords: Aprendizagem dialógica; Ensino de botânica; Taxonomia vegetal; Botany teaching; Dialogic learning; Plant taxonomy; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM